Cancer Associated Fibroblasts Promote Renal Cancer Progression Through a TDO/Kyn/AhR Dependent Signaling Pathway - Chen, Li-bo; Zhu, Shun-ping; Liu, Tian-pei; Zhao, Heng; Chen, Ping-feng; Duan, You-jun; Hu, Rong (Frontiers in Oncology, 2021)
Cancer associated fibroblasts (CAFs) play crucial roles in cancer development, however, the specific mechanisms by which CAFs mediate cancer cells behaviors in renal cancer remain poorly understood. Our study observed enriched CAFs distribution in high degree malignant renal tumor tissues from patients. These CAFs isolated from tumor tissues are prone to facilitate drugs resistance and promote tumor progression both in vitro and in vivo. Mechanistically, CAFs revealed strengthened tryptamine metabolism through a tryptophan 2, 3-dioxygenase (TDO) dependent pathway, resulting in consistent secretion of kynurenine (Kyn). Kyn produced from CAFs could stimulate the expression of aromatic hydrocarbon receptor (AhR), eventually resulting in the AKT and STAT3 signaling pathways activation. Inhibition of AKT signal prevented cancer cells proliferation, while inhibition of the STAT3 signal reverted durgs resistance and cancer migration induced by kynurenine. Application of AhR inhibitor DMF could efficiently suppress distant metastasis of renal cancer cells, and improve anticancer effects of sorafenib (Sor)/sunitinib (Sun), which described a promising therapeutic strategy for clinical renal cancer.